Latest Approved Therapies for Metastatic Melanoma: What Comes Next? - Farid Menaa (Journal of Skin Cancer)
Nowadays, oncogene-directed therapy and immunotherapy represent the two most promising avenues for patients with metastatic melanoma. The recent oncogene-directed therapeutic, vemurafenib, usually produces high level of tumor shrinkage and survival benefits in many patients with B-RA mutant melanomas, although the fast and high degrees of responses are likely short-lived. Conversely, the newly-approved immunotherapeutic, ipilimumab, produces durable responses in patients presenting CTLA-4 T-cell surface protein. Nevertheless, the possible synergy in combining these two therapeutic strategies primarily rely on the rational design of medical protocols (e.g., sequence and timing of agent administration; drug selectivity; compatibility of combined therapies i.e., adoptive T cell or agents, i.e., MEK inhibitor trametinib, PD-1 and PDL-1 blockers). Improved therapeutic protocols shall overcome therapeutic limitations such as the (i) tolerability and safety (i.e., minimal toxic side-effects); (ii) progression free survival (e.g., reduced relapse disease frequency); (iii) duration response (i.e., decreased drug resistance). Eventually, multidisciplinary approaches are still requested (e.g., genomics for personalized medicine, nanomedicine to overcome low free-drug bioavailability and targeting, systematic search of “melanoma stem cells” to enhance the prognosis and develop more valuable theranostics). In this paper, I will mainly present and discuss the latest and promising treatments for advanced cutaneous melanomas.